Auditoría de gestión como herramienta de valuación de los procesos de la compañía de Transportes TIA S.A. del cantón Quevedo, año 2014. - Palma Tuárez, Jorge Heriberto (2015)
This project aims to implement a management audit as a tool for assessing administrative and financial processes of the carrier Aunt. Inc. Walter at avenue Del Quevedo canton Andrade Fajardo 2014, which allowed to determine the level of efficiency and effectiveness and contributed to finding the existing flaw in the processes that take place in the company. Aunt Transport Company. Inc. Founded on October 5, 1965 providing passenger transport services in the area of Quevedo to Guayaquil is legally registered in the Superintendence of Companies. This company at its inception was established for the popular passenger service to Guayaquil Quevedo which renewed its activities in 2010 making its entire fleet of popular service Direct Executive service with modern buses equipped with the best technology and air conditioning. Control audit was conducted using the methodology of COSO and also the descriptive, statistical, analytical and research techniques of observation and interview methods. Besides auditing techniques such as eye check, verbal, written, documentary and physical, which led to evidence and verify hypotheses on the basis of them issue a report, which includes the criteria, opinions and recommendations for based of these the company to take corrective measures. As a result of the process is made possible to detect weaknesses in the financial area , the evaluation gave as a result the company had poor credit in the economy, caused by the lack of a proper feasibility study, this combined with the lack of preforms. He scrutinizing allowed several significant findings reveal the lack of a manual of procedures, lack of control for lack of a department of internal control and documentation disorder shortage of physical space for the administration area.